The Effectiveness of Mathematics Learning with the STEAM Approach in Improving Students' Critical Thinking Skills - Ichsan Ichsan; Mulyati Mulyati; Sonny Yalti Duma; Nirfayanti Nirfayanti (PT. Anagata Sembagi Education, 2024)
This study aims to assess the effectiveness of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in mathematics learning to improve students' critical thinking skills through a literature review method. The STEAM approach integrates various disciplines with the aim of creating relevant and innovative learning experiences, so as to support the development of critical thinking skills. This study utilizes a literature review method, where various sources such as scientific journal articles, academic books, and related publications are analyzed to identify the impact of the STEAM approach on improving students' critical thinking skills in mathematics learning. The analysis was carried out descriptively qualitatively by reviewing the results of previous studies that discussed the implementation of STEAM. Based on this study, it was found that the application of STEAM in mathematics learning consistently had a positive impact on improving students' critical thinking skills. This is due to the nature of the STEAM approach which encourages collaboration, analytical thinking, and the application of theoretical concepts to practical contexts. This study shows that the STEAM approach is effective in developing high-level thinking skills and can be used as an innovative learning model at various levels of education.